1993
DOI: 10.1046/j.1420-9101.1993.6040559.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex allocation variation in Daphnia pulex

Abstract: Duphniu (Crustacea: Cladocera) reproduce by cyclical parthenogenesis in which the sex of offspring is environmentally determined. Although numerous studies have demonstrated that factors such as crowding and short-day photoperiod stimulate male production, there is limited information on variation in allocation to male and female offspring for any species of Duphniu. The present study assessed the presence or absence of male production in 96 isofemale lines (clones) from each of eight populations of Duphniu pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 2 publications
4
87
2
Order By: Relevance
“…Only a fraction of D. pulex are capable of male production, and although the genetic details remain to be worked out, the limited crosses that have been made between maleand nonmale-producing clones appear to be qualitatively consistent with a single-locus model in which individuals with male/female function are either MM or Mm and those incapable of male production are mm, with a dominant allele (or tight linkage group) M conferring the ability to produce males (Innes and Dunbrack 1993;Innes 1997;Tessier and Cáceres 2004). However, none of the significant markers that we identified in obligate asexuals were associated with the ability to produce males (revealed by application of male-inducing methyl farnesoate; Olmstead and Leblanc 2002).…”
Section: Discussionmentioning
confidence: 76%
“…Only a fraction of D. pulex are capable of male production, and although the genetic details remain to be worked out, the limited crosses that have been made between maleand nonmale-producing clones appear to be qualitatively consistent with a single-locus model in which individuals with male/female function are either MM or Mm and those incapable of male production are mm, with a dominant allele (or tight linkage group) M conferring the ability to produce males (Innes and Dunbrack 1993;Innes 1997;Tessier and Cáceres 2004). However, none of the significant markers that we identified in obligate asexuals were associated with the ability to produce males (revealed by application of male-inducing methyl farnesoate; Olmstead and Leblanc 2002).…”
Section: Discussionmentioning
confidence: 76%
“…In most Cladocera, sexual phase and male production begin after several generations of parthenogenetic reproduction with the production of subitaneously developing eggs. Switch to sexual reproduction and resting egg production is generally cued by a number of factors that are indicative of environmental deterioration (i.e., crowding and short-day photoperiod) and by maternal environmental conditions (Stross, 1987;Hobaek and Larsson, 1990;Innes and Dunbrack, 1993;Innes, 1997;LaMontagne and McCauley, 2001;Koch et al, 2009). In the bodrio, a very early investment in sexual reproduction, independent of population density, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Disp and Morg occur in woodlots, while VBA and War ponds are in more open areas. At least a dozen clonal isolates were individually maintained from each of these ponds in synthetic zooplankton media (Lynch et al, 1986) in conditions described elsewhere (Innes & Dunbrack, 1993). Cups of clonal strains were fed 3.5 mL of algal slurry from an aquarium system daily.…”
Section: Clonal Isolatesmentioning
confidence: 99%
“…Studies that have tested for inter-clonal variation in sex ratios have found it, among clones of D. pulex (Innes & Dunbrack, 1993;Innes, 1997;Innes & Singleton, 2000), clones of D. pulicaria , and both clones (Korpelainen, 1986) and populations (Ferrari & Hebert, 1982) of D. magna. In fact, the significant cloneÂdensity interaction affecting sex ratios in the present study was also found to significantly influence sex ratios in other studies on D. pulex (Ruvinsky et al, 1986;Innes & Singleton, 1994) and D. magna (Yampolsky, 1992).…”
Section: Offspring Sex Ratiosmentioning
confidence: 99%
See 1 more Smart Citation